The glutamine-rich domain of the Drosophila GAGA factor is necessary for amyloid fibre formation in vitro, but not for chromatin remodelling. - Agianian, B.; Leonard, K.; Bonte, E.; Van der Zandt, H.; Becker, P.B.; Tucker, P.A. (Journal of Molecular Biology, 1999)
The Drosophila GAGA factor binds specifically to the sequence GAGAG, and synergises with nucleosome remodelling factor to remodel chromatin in vitro. It consists of an N-terminal domain (POZ/BTB) which mediates protein-protein interactions, a central region which contains the DNA-binding domain, and a C-terminal glutamine-rich region. It is shown that the glutamine-rich region is responsible for the formation of fibres in vitro which, on the basis of their tinctorial properties and CD spectra, may be classified as amyloid fibres. A large structural change, probably resulting in beta-sheet structure, is observed upon fibre formation. Mutants containing the central region, either alone or together with the glutamine-rich region, are largely lacking in secondary structure but they bind specifically to the cognate DNA and are able to remodel chromatin in vitro. Consequently, neither the N-terminal domain nor the C-terminal glutamine-rich regions of the GAGA factor are necessary for chromatin remodelling in vitro.